2016
DOI: 10.18632/oncotarget.12420
|View full text |Cite
|
Sign up to set email alerts
|

Ran GTPase promotes cancer progression via Met receptor-mediated downstream signaling

Abstract: It has been shown previously that cancer cells with an activated oncogenic pathway, including Met activation, require Ran for growth and survival.Here, we show that knockdown of Ran leads to a reduction of Met receptor expression in several breast and lung cancer cell lines. This, in turn suppressed HGF expression and the Met-mediated activation of the Akt pathway, as well as cell adhesion, migration, and invasion. In a cell line model where Met amplification has previously been shown to contribute to gefitini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 40 publications
(59 reference statements)
3
47
0
Order By: Relevance
“…RAN is a small GTPase of the RAS superfamily and is involved in several biological processes, such as nucleocytoplasmic transport, nuclear envelope formation, and mitotic spindle assembly . Moreover, overexpression of RAN has already been reported in myriad of cancers, which is also correlated with poor prognosis, increased aggressiveness, and metastasis, inhibition of which can lead to suppression of cancer . Therefore, to precisely address the oncogenic role of RAN in tumorigenesis of fibrosarcoma, which we found to be upregulated in fibrosarcoma as well.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…RAN is a small GTPase of the RAS superfamily and is involved in several biological processes, such as nucleocytoplasmic transport, nuclear envelope formation, and mitotic spindle assembly . Moreover, overexpression of RAN has already been reported in myriad of cancers, which is also correlated with poor prognosis, increased aggressiveness, and metastasis, inhibition of which can lead to suppression of cancer . Therefore, to precisely address the oncogenic role of RAN in tumorigenesis of fibrosarcoma, which we found to be upregulated in fibrosarcoma as well.…”
Section: Resultsmentioning
confidence: 85%
“…[33][34][35] Moreover, overexpression of RAN has already been reported in myriad of cancers, which is also correlated with poor prognosis, increased aggressiveness, and metastasis, [36][37][38] inhibition of which can lead to suppression of cancer. 39 Therefore, to precisely address the oncogenic role of RAN in tumorigenesis of fibrosarcoma, which we found to be upregulated in fibrosarcoma as well. We cotransfected RAN along with miR-197-3p mimic in fibrosarcoma cells and observed that restoration of miR-197-3p abrogated the effect of RAN on cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 94%
“…Gene ontology and KEGG pathways for these 24 genes were then performed using the web‐based online pathway tool NIH‐DAVID (Table) . Among KEGG pathways for the 24 genes, the RNA transport pathway was attractive as a therapeutic target because it included XPO1 and RAN , which are well characterized therapeutic targets for human cancers, including lung cancer . Our screening studies identified eIF2 β as an additional gene of the RNA transport pathway.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Among KEGG pathways for the 24 genes, the RNA transport pathway was attractive as a therapeutic target because it included XPO1 and RAN, which are well characterized therapeutic targets for human cancers, including lung cancer. [8][9][10][11] Our screening studies identified eIF2b as an additional gene of the RNA transport pathway. This gene encodes the b-subunit of EIF2, which is a heterotrimeric G protein comprising a-, band c-subunits, and functions as a translation initiator factor.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation